Comprehensive risk reduction in patients with atrial fibrillation: emerging diagnostic and therapeutic options$da report from the 3rd Atrial Fibrillation Competence NETwork/European Heart Rhythm Association consensus conference - Kirchhof, Paulus; Dobrev, Dobromir (Europace, 2012)
Abstract. While management of atrial fibrillation (AF) patients is improved by guideline-conform application of anticoagulant therapy, rate control, rhythm con
Published: 26 July 2011
Gesehen am 29.11.2018